Use of activated charcoal in a solid-phase extraction technique for analysis of pesticide residues in tomatoes - Kaipper,Beatriz I. A. (2001)
The present work describes extraction and purification methods that were developed to determine and to monitor the content of organophosphorus pesticides in tomato crops from the agricultural district of Florianópolis, Brazil. SPE technique with activated charcoal was used for purification and recovery of the pesticides methamidophos, acephate, malation and methyl parathion. The solvents used for sample extraction and elution were chosen after several comparative tests. Best results were achieved using ethyl acetate for extraction and dichloromethane - ethyl acetate (7:3) for elution. Average recoveries from the matrices fortified with 0.20 to 0.60 mug g-1 ranged from 85.2 to 100 % with overall coefficients of variation of 1.3 to 6.3 %. The limits of detection of the method varied between 0.04 and 0.12 ng g-1. Activated charcoal demonstrated to be efficient for tomato matrix purification and for quantitative recovery of the analytes.